Evidence for natural reassortants of human rotaviruses belonging to different genogroups. - Ward, R L (1990)
Of 335 rotavirus isolates associated with diarrheal disease in Bangladesh that were culture adapted and subsequently characterized for electropherotype, subgroup, and serotype, 9 had properties that suggested they may be natural reassortants between human rotaviruses belonging to different "genogroups." Two of these were examined in greater detail by RNA-RNA hybridization with prototype strains representative of each of the three proposed human rotavirus genogroups. One subgroup II isolate, 248, with a "long" electrophoretic pattern was neutralized by hyperimmune antisera to both serotype 2 and 4 strains. Consistent with these results, seven RNA segments of this isolate formed hybrids with human strains belonging to the Wa genogroup and four segments hybridized with strains belonging to the DS-1 genogroup. The second isolate examined, 456, belonged to subgroup II and had a long electrophoretic pattern but was found to be a serotype 2 strain. This isolate also appeared to be an intergenogroup reassortant because three of its segments formed hybrids with strains belonging to the Wa genogroup and eight hybridized with viruses of the DS-1 genogroup. On the basis of the relative migration rates of these RNA-RNA hybrids during gel electrophoresis, a suggested origin for each gene segment was proposed which was consistent with the results expected from electrophoretic, subgroup, and serotypic analyses.